Applying Occam's Razor and Descending the Reconstructive Ladder: The Modified Cheek Advancement Flap for Reconstruction of Nasal Defects - Himeles, Jaclyn Rosenthal; Criscito, Maressa C.; Kellner, Rebecca; Lee, Nayoung; Stevenson, Mary L.; Sclafani, Anthony P.; Carucci, John A. (Facial Plastic Surgery, 2022)
Nasal reconstruction has important functional and cosmetic considerations, as proper repair of nasal defects is necessary to maintain function of the nasal airway and to recreate the normal appearance of this central facial structure. Cheek advancement flaps provide matched, mobile, and highly vascularized tissue for the reconstruction of nasal defects, allowing for the concealment of incisions within natural creases in a one-stage approach. However, cheek advancement flaps are often underutilized for nasal reconstruction because of their difficulty in restoring nasal contour. We describe reconstruction of 19 nasal dorsal and sidewall defects 0.8 to 3 cm in size. We incorporated a periosteal anchoring suture to maintain/restore nasal contour and additionally removed a half standing cone inferior to the defect to prevent encroachment of the nasal ala or alar crease. All patients were evaluated at least 3 months postoperatively. In all patients, we were able to restore concavity of the nasofacial sulcus, preserve the biconvex nasal tips, prevent alar flaring and retraction, and conserve the alar groove. All patients had excellent functional and cosmetic outcomes. We believe this modified cheek advancement flap provides functionally and aesthetically superior results and can be considered as a first-line approach for repair of nasal dorsal and sidewall defects in subselected patients.
Keywords: Mohs micrographic surgery; nasal reconstruction; advancement flap